ANALISIS TINGKAT KESEHATAN BANK SEBELUM DAN SESUDAH KONSOLIDASI - Jayanthi Shekarmodo Jawotho (2022)
The purpose of this study was conducted to determine differences in the of Bank health level before and after consolidating using the Risk-Based Bank Branch (RBBR) method. In this study, the Bank health level uses four variables, namely risk profile, good corporate governance (GCG), profit (profitability), and capital (capitalization). This research uses Banking companies that are consolidating with the aim of meeting the minimum core capital of Banks according to the Financial Services Authority Regulation concerning the Consolidation of Commercial Banks of 20 Banks, with the end of the study as many as 15 Banks. The study uses secondary data with a sample collection method using purposive sampling. The data analysis technique used in this study was the wilcoxon signed rank test, with the help of the SPSS 25.0 application. The results of these test indicate that (1) the risk profile before and before consolidation is different, (2) the good corporate governance (GCG) before and before consolidation is not different, (3) the earnings (profitability) before and before consolidation is not different, (4) the capital (capitalization) before and before consolidation is different.